2022
DOI: 10.1097/wnn.0000000000000302
|View full text |Cite
|
Sign up to set email alerts
|

White Matter, Behavioral Neurology, and the Influence of Corticocentrism

Abstract: White matter in the human brain occupies roughly the same volume as gray matter but has received far less attention in behavioral neurology and related disciplines. In particular, the cerebral cortex has long dominated thinking about the organization of brain-behavior relationships. As a result, subcortical structures, including deep gray matter and, most notably, white matter, have been accorded relatively little neuroscientific study compared with the extensive work devoted to the cerebral cortex. The influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In a previous prospective study, researchers adminstered patients with oral anti-anxiety drugs before they underwent abdominal surgery, which could effectively reduce the incidence of postoperative cognitive function [26]. Preoperative anti-anxiety therapy may be an effective means to prevent postoperative cognitive function [27,28], and in correlation analysis, the preoperative SAS score is positively correlated with the MMSE score. Therefore, the preoperative SAS score can re ect the postoperative cognitive dysfunction index, and preoperative active anti-anxiety treatment may effectively prevent postoperative cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous prospective study, researchers adminstered patients with oral anti-anxiety drugs before they underwent abdominal surgery, which could effectively reduce the incidence of postoperative cognitive function [26]. Preoperative anti-anxiety therapy may be an effective means to prevent postoperative cognitive function [27,28], and in correlation analysis, the preoperative SAS score is positively correlated with the MMSE score. Therefore, the preoperative SAS score can re ect the postoperative cognitive dysfunction index, and preoperative active anti-anxiety treatment may effectively prevent postoperative cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive slowing stands as the primary manifestation of white matter impairment, stemming from compromised impulse transmission due to damaged myelin and, in some cases, axonal injury. This impairment also extends to executive function, memory retrieval, sustained attention, and an array of psychiatric disorders [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…WMH can be classified into periventricular WMH in the adjacent location and WMH in the deep subcortical white matter near the lateral ventricles. Because periventricular nerve fibers link the cortex to subcortex and other more distant brain regions, and are more susceptible to fluid mechanics changes in distal arteries, cognitive functional impairment induced by periventricular WMH is more pronounced than impairment in non-periventricular areas [27][28] . Biesbroek et al [19] identified prethalamic radiation and WMH in the corpus callosum area as one of the main symptoms of imaging pathological changes resulting in reduced execution, memory and visual motor speed.…”
Section: White Matter Hyperintense Signal (Wmh) and Cognitive Dysfunc...mentioning
confidence: 99%